Czym jest sakralny wymiar natury? Filozoficzna interpretacja twórczości Friedricha Hölderlina w dziełach Romano Guardiniego - Andrzej Kobyliński (Studia Philosophiae Christianae)
The principal objective of this article is to introduce the sacred realm of nature, discussed by Romano Guardini (1885–1968) in the philosophical works he devoted to the interpretation of the writings of Friedrich Hölderlin (1770–1843). Guardini conducted his research on Hölderlin’s output in the philosophy of religion. With respect to Hölderlin’s poems, Guardini noted the special role played in them by nature understood as the space inhabited by the sacrum. In fact, Hölderlin’s literary works are pervaded with a new form of Post-Christian religiosity, which consists in the practice of re-interpreting Christian symbols and translating the religious phenomenon from one objective reality to various, individualized forms.